Obstetric outcome of antenatal mother with history of spontaneous abortion attending a tertiary care hospital in Puducherry - G., Vijayalakshmi; Nirmala, Jaget; G., Sindhuja Sekar; R., Priyanka (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: The pregnancy time is critical for both the mother’s and the baby’s health. The most common unfavourable pregnancy outcome is spontaneous abortion. Spontaneous pregnancy loss is a surprisingly common event, with roughly 15% of all clinically diagnosed pregnancies ending in pregnancy failure. Couples who suffer from frequent miscarriages may find it difficult to cope physically and emotionally. This study was planned to evaluate the association of preterm delivery, low birth weight, IUGR, recurrence of abortion, still birth, IUD, PROM, or any other adverse outcome in patients with history of previous spontaneous abortions. Objectives were to look for association between previous spontaneous abortion and preterm delivery, low birth weight, IUGR, recurrence of abortion, stillbirth, IUD, PROM and other complications in subsequent pregnancies. Methods: This was a prospective observational study done with 150 samples. The information such as demographic data of the antenatal women, clinical history, past obstetrics history, clinical examination, laboratory investigations and outcome of present pregnancy were collected and evaluated. Results: Maternal complications such as UTI (4.6%), Infection and fever (5.3%), PROM (2.7%), PPH (4%), hyperemesis 4%, PPROM 2.7% were observed. In study population, 60% of the foetus were in cephalic position, 19% in breech presentation and 21% in shoulder presentation. 29% of the women had preterm delivery, 34% were delivered by LSCS and 6% had spontaneous abortions. Low birth weight babies delivered in 25% cases. Foetal distress was observed in 15%, FGR in 9%, still birth in 3% and IUD in 1%. Conclusions: Women with previous spontaneous abortion are associated with a higher incidence of preterm delivery, cesarean section rate, neonatal low birth weight, fetal distress and high possibility of infection. Therefore, patients with previous spontaneous miscarriage represent a high-risk population for obstetric complication and close surveillance during the antenatal period is required.